The reformed theology of Benjamin Keach (1640-1704) - Arnold, J; Jonathan W Arnold (2010)
Benjamin Keach, the most prolific Particular Baptist theologian of the seventeenth century, described himself as a defender of ‘Reformed Orthodoxy’. Despite this self-identification, modern scholarship has largely relegated Keach to a self-educated dissenting pastor whose major achievement could be found in his controversial support of hymn singing. Two recent dissertations have attempted to revise this view of Keach, but no scholarly work has yet attempted to wrestle holistically with Keach’s view of himself as a Reformed theologian. This work fills that void by reviewing Keach’s own understanding of the term ‘Reformed Orthodoxy’, reconstructing Keach’s connections both in the personal contacts available in dissenting London and Buckinghamshire and in the books at his disposal, examining the major aspects of his theology, and placing that theology within the spectrum of Reformed Orthodoxy. From the time of his entry onto the public theological stage, Keach quickly became identified with those with whom he networked intellectually. From his branding as a Fifth Monarchist to his identification first as a General Baptist and later as the most prominent Particular Baptist, those connections proved to be the most idiosyncratic characteristic of Keach’s theological pilgrimage. Those connections crossed the conventional lines of systematic theology and boundaries of religious sects, resulting in Keach’s theology crossing those same lines yet remaining Reformed in its major assertions. Following the organizational structure of Keach’s catechisms and confessions, this work proceeds by expounding and interrogating Keach’s major theological positions—his understanding of the Trinity including this doctrine’s foundational role in ecclesiology, the significance of the covenants, justification, and eschatology. Throughout this exposition, Keach’s theological lenses, shaped by his contacts and his independent, creative thought, become clear. Ultimately, Keach proves himself to be a capable Reformed theologian, able and willing to dialogue with the most influential theologians, yet consistently forging his own ground within Reformed Orthodoxy as a whole and more specifically Particular Baptist theology.